1990
DOI: 10.1080/01971529008055047
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Immunoassay to Measure Low Levels of Haptoglobin in Biological Fluids

Abstract: A novel immunoenzymatic assay is described for the quantitation of human haptoglobin (Hp). Two binding sites on the Hp molecule, namely for hemoglobin (Hb) and for the specific antibody, are involved in the reaction. Hb adsorbed onto the polystyrene microplate binds Hp present in any biological fluid. The formed Hp-Hb complex is detected with horse-radish peroxidase conjugated with anti-Hp antibody. By means of this ELISA, Hp may be measured in the range of 5 to 150 micrograms/L. Comparison of the Hp-ELISA wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…An alternative arrangement was first described by Kątnik and Dobryszycka (1990) which utilizes the ability of Hp to bind Hb. These authors developed an ELISA to detect Hp in human biological fluids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative arrangement was first described by Kątnik and Dobryszycka (1990) which utilizes the ability of Hp to bind Hb. These authors developed an ELISA to detect Hp in human biological fluids.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA for human haptoglobin (Kątnik and Dobryszycka 1990) was modified for bovine Hp determination. Two variants of ELISA were conducted.…”
Section: Hp Concentration Measurements Guaiacol Methodsmentioning
confidence: 99%
“…We also demonstrated some differences in the quantitation of haptoglo in in pathological body fluids, between the "traditional" Hp-Hb method and the method based on Hp-concanavalin A complex formation (7). The purpose of the present study was to investigate whether these reactivities of haptoglobin, as determined in the sera of patients with ovarian tumours, might be used as an index of disease activity.…”
Section: Introductionmentioning
confidence: 99%
“…This might be at least partially explained by the difficulties in determination of the acute phase protein in the oral cavity due to their low concentrations (Backhausz, 1975;Grimoud, 1998;Katnik, 1990;Keur, 1994). Some authors reported immunoenzyme method to determine haptoglobin in different biofluids, including saliva, which ranged 5 to 150 μg/l (Katnik, 1990). The salivary haptoglobin measurement is commonly used in the veterinary practice (Hiss, 2003;.…”
Section: Haptoglobinmentioning
confidence: 99%
“…There are a limited number of studies regarding the salivary haptoglobin (Backhausz, 1975;Grimoud, 1998;Katnik, 1990). This might be at least partially explained by the difficulties in determination of the acute phase protein in the oral cavity due to their low concentrations (Backhausz, 1975;Grimoud, 1998;Katnik, 1990;Keur, 1994). Some authors reported immunoenzyme method to determine haptoglobin in different biofluids, including saliva, which ranged 5 to 150 μg/l (Katnik, 1990).…”
Section: Haptoglobinmentioning
confidence: 99%